International and intra-national technology spillovers and technology development paths in developing countries: The case of China - Miao Fu; Xiaolan Fu; Tieli Li (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2008)
This paper analyses the paths of technology development among regions with heterogeneous economic and technological characteristics, focusing on the case of China. It finds that intra-national technology transfer, that is, the technology transfer from technologically advanced provinces to less advanced ones, is more important than that taking place through FDI in the backward regions. In technologically advanced areas, learning by doing, indigenous R&D and technology transfer from FDI all play a significant role in technical progress. The relationship between the strength of interprovincial technology transfer and technological distance is U-shaped, with the technology threshold falling outside the upper bound of technology distance. This suggests that technology transfer takes place more effectively when technological distance is small. The paper finds that learning by doing and R&D are important internal routes to technical progress. R&D plays a key role in the assimilation of foreign technologies, whereas learning by doing is relevant for the absorption of interprovincial technology transfers.
Keywords: O14; O32; 330; FDI; technology spillovers; technology threshold; Technologietransfer; Spillover-Effekt; Technischer Fortschritt; Direktinvestition; China